A Legal Analysis of Changes to the Severance Pay Calculation Formula - Muhammad Arif; Ending Solehudin (Program Pascasarjana UIN Sumatera Utara Medan, 2025)
Fundamental changes in the termination compensation scheme following the enactment of the omnibus law have triggered a reorientation of workers' rights protection in Indonesia. This study aims to examine the legal transformation of the severance pay calculation formula from Law Number 13 of 2003 to Law Number 6 of 2023 concerning Job Creation. Using normative legal research methods with a statute approach and a conceptual approach, this study analyzes the implications of this shift in norms for the certainty of workers' rights. The results show that this transformation not only changes the nominal value by reducing the multiplier but also shifts the protection paradigm from job security to flexibility. The correlation between the decline in severance pay and the certainty of workers' rights indicates a degradation of economic value that has not been fully compensated by the job loss insurance program. Furthermore, an analysis of the Constitutional Court's ruling emphasizes the importance of the constitutionality of norms that must balance investment facilitation with the right to a decent living. This study concludes that regulatory synchronization following the Constitutional Court's ruling is crucial to prevent legal uncertainty that harms industrial stability and worker welfare.